Perlindungan Hukum Anak Hasil Perkawinan Siri Bagi Orang Islam Setelah Terjadinya Itsbat Nikah - Erha Sena; Endang Sulistyaningsih; Sunarya Raharjo (Fakultas Hukum Universitas Janabadra, 2026)
Unregistered marriages often cause problems related to the legal status of their children, because children born in unregistered marriages are illegitimate children who only have a civil relationship with their mother, so to overcome this, Itsbat Nikah is needed so that Siri Marriage becomes a legal Marriage that has permanent legal certainty. This study aims to determine the Protection of Children's Rights from Siri Marriages for Muslims After the Itsbat Nikah occurs. The research approach used is the normative juridical approach. Data collection techniques in this study were carried out by combining library study methods and interviews with informants. The results of research in the Religious Courts throughout DIY show that this process provides legal certainty, protecting Children's Rights. Marriage Confirmation plays a crucial role in issuing or amending a child's birth certificate. The requirement for issuing a certificate is a marriage license or the parents' marriage certificate. Therefore, if a Marriage Confirmation Decision has been issued, the parties can issue their marriage certificate at the Office of Religious Affairs (KUA). This will declare the marriage valid, and the birth certificate of the child born within the marriage will be declared valid and establish a civil relationship with the father and mother).